"Learning to Be Myself": Paths 2 the Future Career Development Curriculum for Young Women With Disabilities. (August 2019) - Lindstrom, Lauren; Hirano, Kara A.; Ingram, Angela; DeGarmo, David S.; Post, Cindy
Young women with disabilities often experience limited career options and opportunities. This study provides an overview and preliminary results from the "Paths 2 the Future" (P2F) curriculum designed to meet the unique career development needs of young women with disabilities. P2F includes 75 lessons covering topics of self-awareness, disability knowledge, gender identity, and career and college readiness. Survey data were collected from young women with learning, health, intellectual, and emotional disabilities who participated in the curriculum in four high schools ( N = 49). Paired sample t tests documented significant improvements from pretest to posttest scores for disability and gender awareness, vocational skills self-efficacy, self-realization, and an overall career development construct. Focus groups were conducted to gather feedback on participant experiences. Young women in the focus groups noted the unique benefits of a "girls only" class and described increases in self-awareness and personal empowerment.